Heterovalent chalcogen bonding: supramolecular assembly driven by the occurrence of a tellurium(ii)⋯Ch(i) (Ch = S, Se, Te) linkage. Issue 21 (20th September 2022) - Torubaev, Yury V.; Rozhkov, Anton V.; Skabitsky, Ivan V.; Gomila, Rosa M.; Frontera, Antonio; Kukushkin, Vadim Yu.
Abstract : The revealed heterovalent Te II ⋯Ch I (Ch = S, Se, Te) chalcogen bonding was used for targeted noncovalent integration of two Ch centers in different oxidation states. Abstract : The dichalcogenides Ph2 Ch2 (Ch = S, Se, Te) were cocrystallized with perfluorinated chalcogen bond donors Tol F 2 Te and Py F 2 Te (Tol F = 4-CF3 C6 F4, Py F = 4-NC5 F4 ) to obtain the 1 : 1 cocrystals Tol F 2 Te·Ph2 Ch2 (Ch = S 1, Se 2, Te 3 ) and Py F 2 Te·Ph2 Se2 (4 ). In the X-ray structures of 1–4, heterovalent Te II ⋯Ch I (Ch = S, Se, Te) chalcogen bonding was identified on consideration of the geometrical parameters and, in addition, based on the results of appropriate density functional theory (DFT) calculations including quantum theory of atoms-in-molecules (QTAIM), noncovalent interaction plot (NCIplot) analysis, molecular electrostatic potential surfaces (MEP), and atoms-in-molecules (AIM) charge analysis. The binding energy in the dimeric structure is in the range between −9.7 and −12.9 kcal mol −1, where the contribution of the heterovalent chalcogen bonding ranges from −4.7 to −6.5 kcal mol −1 . In the Te II ⋯Ch I moiety, the Te II center plays the role of an electrophilic partner, while the chalcogens in the lower oxidation state, 1+, exhibit nucleophilic properties. The heterovalent Te II ⋯Ch I (Ch = Se, Te) chalcogen bonding was thus used for the targeted noncovalent integration of two Ch centers in different oxidation states.